THE EFFECT OF RISK-BASED INTERNAL AUDIT (RBIA) IMPLEMENTATION ON AUDIT QUALITY DURING THE COVID-19 PANDEMIC - Suprayogi, Bambang; Habiburahman, Habiburahman; Nilwan, Afrizal (Program Studi Magister Manajemen, 2024)
The goal of this study was to ascertain whether the deployment of risk-based internal audits at the National Social Security Agency for Employment or BPJS Ketenagakerjaan has an impact on audit quality during the Covid-19 pandemic. The subject of this study was a sample of 73 respondents who worked as auditors for the National Social Security Agency for Employment or BPJS Ketenagakerjaan Internal Supervisory Unit. Based on the findings of this research, the use of risk-based internal audit with indicators identifying universal audit, type of audit, risk audit, data nature audit, and these three intensity positions during the Covid-19 pandemic. During the pandemic, there was a positive and significant impact on the quality of audits at the BPJS Employment Internal Monitoring Unit, the National Social Security Agency for Employment. Changes to audit rules, as well as artificial intelligence training, network security and development of data functions, can all be done to improve the quality of auditor human resources and combat the impact of Covid 19 on audit quality.